(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study investigates the effect of the role-play technique on the development of oral speech in French language learning among beginner-level students. Using a task-based instructional approach, students participated in structured role-play activities designed to enhance their speaking skills. A pre-test and post-test were administered to evaluate the learners’ progress in oral proficiency. The results indicate a significant improvement in students’ fluency, vocabulary usage, and confidence after the implementation of role-plays. These findings support the integration of interactive, communicative methods in beginner-level foreign language instruction.